Implementasi Nilai-Nilai Karakter Dalam Pembelajaran Bahasa Indonesia Untuk Meningkatkan Sikap Positif Siswa - Wahyuni, Sri; Amrulloh, Roni; Hamdi, Zulfadli (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: Indonesian language learning has not been optimal in instilling character values. Students still often lack discipline, procrastinate on assignments, and lack responsibility. This occurs because learning emphasizes cognitive aspects rather than the formation of attitudes and character values. This study aims to: 1) Identify effective strategies in integrating character values ​​in Indonesian language learning at SDN 4 Menceh. 2) Analyze the challenges faced in implementing character values ​​in Indonesian language learning at SDN 4 Menceh. 3) Evaluate the impact of implementing character education-based Indonesian language learning on students' positive attitudes. This study used a qualitative approach with data collection techniques of observation, interviews, and documentation. Data sources were the principal, teachers, and third-grade students of SDN 4 Menceh. The results showed that the implementation of character values ​​in Indonesian language learning for third-grade students of SDN 4 Menceh was quite effective. The strategies used included active learning, group discussions, story-based learning, and teacher role models in terms of discipline, responsibility, and cooperation. The obstacles faced were differences in student character, limited time and resources, but most students still showed active participation, discipline, responsibility, and cooperation, so that character values ​​could begin to form in the learning process. Abstrak: Pembelajaran Bahasa Indonesia belum optimal dalam menanamkan nilai karakter. Siswa masih sering kurang disiplin, menunda tugas, dan kurang bertanggung jawab. Penelitian ini bertujuan untuk 1) Mengidentifikasi strategi yang efektif dalam mengintegrasikan nilai-nilai karakter dalam pembelajaran Bahasa Indonesia di SDN 4 Menceh. 2) Menganalisis tantangan yang dihadapi dalam implementasi nilai-nilai karakter pada pembelajaran Bahasa Indonesia di SDN 4 Menceh. 3) Mengevaluasi dampak penerapan pembelajaran Bahasa Indonesia berbasis pendidikan karakter terhadap sikap positif siswa. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data observasi, wawancara dan dokumentasi. Sumber data adalah kepala sekolah, guru dan siswa kelas 3 SDN 4 Menceh. Hasil penelitian menunjukkan bahwa implementasi nilai-nilai karakter dalam pembelajaran Bahasa Indonesia di kelas III SDN 4 Menceh berjalan cukup efektif. Strategi yang digunakan meliputi pembelajaran aktif, diskusi kelompok, pembelajaran berbasis cerita, serta keteladanan guru dalam bersikap disiplin, bertanggung jawab, dan bekerja sama. Kendala yang ditemui berupa perbedaan karakter siswa, keterbatasan waktu, dan sumber daya, namun sebagian besar siswa tetap menunjukkan partisipasi aktif, kedisiplinan, tanggung jawab, dan kerja sama, sehingga nilai-nilai karakter dapat mulai terbentuk dalam proses pembelajaran.